Italian organisations within the European nanotechnology network: presence, dynamics and effects - Calignano, Giuseppe (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Nanotechnology is an emerging interdisciplinary field that, according to the European Commission, represents one of the world’s new technological frontiers. Nanoscience and nanotechnology play a key role in European Union research policies; they have been included among the “seven priority thematic areas” of the Sixth Framework Programme and the “nine themes” of the Cooperation Programme of the Seventh Framework Programme. The purpose of this study is to assess the role of Italian organisations in the existing European nanotechnology innovation network and to illuminate several aspects of relational and geographical dynamics as well as the scientific and economic effects of these partnerships in Italy. Using an official document issued by the European Commission entitled “Mapping Portal for Nanotechnology Research” and adopting social network analysis techniques, statistics and qualitative interviews, it is determined that Italy plays a central role in the European nanotechnology network, that Italian organisations have tended to replicate satisfactory prior collaborations, that other factors have been more significant than geographical proximity in creating research groups and developing projects, and, finally, that scientific effects have been substantially more significant than economic effects at the national level.